Perancangan Sistem Informasi Persediaan Pada Toko Cat Berbasis Web (Studi Kasus: Akira Paintstore Pamulang) - Julianus Alfario; Sartika Lina Mulani Sitio (CV. Multi Kreasi Media, 2024)
Inventory of goods is one of the important roles for the sales process at the paint shop. For this reason, the use of computers is very helpful in data processing work. Inventory data processing carried out at the Akira Paintstore Pamulang paint shop still uses manuals such as recording in a book, resulting in a problem that affects the existing information, including the problem of the inventory storage system still using the manual method or how to record in a book so it is less efficient, inventory data goods are still often lost or mixed up because they still use the manual method of recording in the book, the reports are still less efficient and less tidy because they still use the manual method. This study aims to design a system that can provide updated information and reduce errors in inputting so as to make it easier for workers at this paint shop to process item data. The writing method in this research is the waterfall method and for system procedures using UML (Unified Modeling Language), which is implemented in the PHP programming language with Sublime Text and database creation on MYSQL so that it can create web-based inventory applications.